INVESTIGATING REITERATION IN ENGLISH AND ARABIC ADVERTISEMENTS (A CONTRASTIVE ANALYSIS) - Ibrahim, Atyaf Hasan (PEOPLE: International Journal of Social Sciences, 2017)
Language is used by people in everyday life situations. They use it to convey their thoughts to each other about different aspects of life. Advertising is one of the methods used by humans to convey messages through language. It uses language in a way that can be effective and sensible to the readers and the audience. In doing so, it must be lexically cohesive. To achieve this cohesion, the researcher will explore a number of cohesive ties known as reiteration that can be used to link the ideas of the advertisement together in order to get the meaning intended. The term ‘lexical cohesion’ may be referred to as "lexicalization" highlighting the functions and roles of using the lexical devices in designing and producing advertisements such as the use of "repetition, synonymy, general words, super- ordinate, etc…". This study is an attempt to touch upon the lexical cohesion of the English and Arabic advertisements conducted by the use of reiteration. Besides, it aims at finding out the similarities and differences between the two languages concerning their use of the lexical cohesive ties in advertisements. The researcher sites samples of English and Arabic advertisements for the analysis. The samples are taken from magazines, journals and net concerned with cosmetics, food, tourism, etc. for the variety of samples. The model adopted for the analysis is Halliday and Hassan's. The principal objectives of the study were as follows: 1) What are the differences and similarities existing between the use of reiteration as lexical cohesive ties in English and Arabic advertisements? 2) Which type of reiteration is more used than other types?